Evaluating the capabilities of high-resolution PlanetScope and Sentinel-2 images for mapping burned area and vegetation regrowth in Indonesia’s savannas - Yenni Vetrita; Karunika Diwyacitta; Krisna Malik Sukarno; Israr Albar; Ahmad Basyiruddin Usman; Rasis Putra Ritonga; Imam Santoso; Anugrah Indah Lestari; Tatik Kartika; Dandy Aditya Novresiandi; Indah Prasasti; Kurnia Ulfa; et al. (International Journal of Remote Sensing, 2025)

Classification of direct threats to the conservation of ecosystems and species 4.0 - Nick Salafsky; Claire Relton; Bruce E. Young; Philippe Lamarre; Monika Böhm; Maxime Chénier; Erica Cochrane; Mark Dionne; Kevin K. He; Craig Hilton‐Taylor; Charles Latrémouille; John Morrison; et al. (Conservation Biology, 2025)
Identifying and assessing the magnitude of direct threats to ecosystems and species are critical steps to prioritizing, planning, implementing, and assessing conservation actions. Just as medical clinicians and researchers need a standard way to talk about human diseases, conservation practitioners and scientists need a common and comprehensive language to talk about the threats they are facing to facilitate joint action, evaluation, and learning. To meet this need, in 2008 the IUCN Species Survival Commission and the Conservation Measures Partnership produced the first version of a common threats classification with the understanding that it would be periodically updated to take into account new information and learning. We present version 4.0 of this classification. For this latest update, we reviewed existing versions and derivatives of the original classification, over 1000 citations of the classification, threats data from over 2900 real‐world conservation projects, and comments from many users. Based on our findings, we made changes to the threats classification scheme, including addition of a level 0 threat class, refinement of levels 1 and 2 threat categories, and addition of the threat “Fencing & walls” to level 2. Also added were level 3 threat types and modifiers that provide a more detailed description of different types of direct threats and thus allow users to fine‐tune analyses and actions. The update also clarifies how to treat various stressors, including natural disaster events and climate change. As a result of these changes, we revised the formal definition of direct threats. They include human actions that are the direct cause of ecosystem or species‐population degradation and loss, such as agriculture, transport, natural resource use, and ecosystem management. They also include ultimate stressors in natural systems whose dynamics have been altered by the effects of current or historical human actions, such as invasive or problematic native species, pollution, natural disasters, and climate change.

Machine-learning based spatiotemporal performance analysis of degraded tropical peatland groundwater level numerical model - Iman Salehi Hikouei; Keith N. Eshleman; Bambang Hero Saharjo; Laura L.B. Graham; Grahame Applegate; Mark A. Cochrane (Groundwater for Sustainable Development, 2025)

Aboveground biomass modeling using simulated Global Ecosystem Dynamics Investigation (GEDI) waveform LiDAR and forest inventories in Amazonian rainforests - Nadeem Fareed; Izaya Numata; Mark A. Cochrane; Sidney Novoa; Karis Tenneson; Antonio Willian Flores de Melo; Sonaira Souza da Silva; Marcus Vinicio Neves d’ Oliveira; Andrea Nicolau; Brian Zutta (Forest Ecology and Management, 2025)

Replanting and yield increase strategies for alleviating the potential decline in palm oil production in Indonesia - Jing Zhao; Andrew J. Elmore; Janice Ser Huay Lee; Izaya Numata; Xin Zhang; Mark A. Cochrane (Agricultural Systems, 2023)

Using machine learning algorithms to predict groundwater levels in Indonesian tropical peatlands - Iman Salehi Hikouei; Keith N. Eshleman; Bambang Hero Saharjo; Laura L.B. Graham; Grahame Applegate; Mark A. Cochrane (Science of The Total Environment, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Critical land change information enhances the understanding of carbon balance in the United States - Jinxun Liu; Benjamin M. Sleeter; Zhiliang Zhu; Thomas R. Loveland; Terry Sohl; Stephen M. Howard; Carl H. Key; Todd Hawbaker; Shuguang Liu; Bradley Reed; Mark A. Cochrane; Linda S. Heath; et al. (Global Change Biology, 2020)
Large‐scale terrestrial carbon (C) estimating studies using methods such as atmospheric inversion, biogeochemical modeling, and field inventories have produced different results. The goal of this study was to integrate fine‐scale processes including land use and land cover change into a large‐scale ecosystem framework. We analyzed the terrestrial C budget of the conterminous United States from 1971 to 2015 at 1‐km resolution using an enhanced dynamic global vegetation model and comprehensive land cover change data. Effects of atmospheric CO 2 fertilization, nitrogen deposition, climate, wildland fire, harvest, and land use/land cover change (LUCC) were considered. We estimate annual C losses from cropland harvest, forest clearcut and thinning, fire, and LUCC were 436.8, 117.9, 10.5, and 10.4 TgC/year, respectively. C stored in ecosystems increased from 119,494 to 127,157 TgC between 1971 and 2015, indicating a mean annual net C sink of 170.3 TgC/year. Although ecosystem net primary production increased by approximately 12.3 TgC/year, most of it was offset by increased C loss from harvest and natural disturbance and increased ecosystem respiration related to forest aging. As a result, the strength of the overall ecosystem C sink did not increase over time. Our modeled results indicate the conterminous US C sink was about 30% smaller than previous modeling studies, but converged more closely with inventory data.

Dynamics of a human‐modified tropical peat swamp forest revealed by repeat lidar surveys - Béatrice Wedeux; Michele Dalponte; Michael Schlund; Stephen Hagen; Mark Cochrane; Laura Graham; Aswin Usup; Andri Thomas; David Coomes (Global Change Biology, 2020)
Tropical peat swamp forests (PSFs) are globally important carbon stores under threat. In Southeast Asia, 35% of peatlands had been drained and converted to plantations by 2010, and much of the remaining forest had been logged, contributing significantly to global carbon emissions. Yet, tropical forests have the capacity to regain biomass quickly and forests on drained peatlands may grow faster in response to soil aeration, so the net effect of humans on forest biomass remains poorly understood. In this study, two lidar surveys (made in 2011 and 2014) are compared to map forest biomass dynamics across 96 km 2 of PSF in Kalimantan, Indonesia. The peatland is now legally protected for conservation, but large expanses were logged under concessions until 1998 and illegal logging continues in accessible portions. It was hypothesized that historically logged areas would be recovering biomass while recently logged areas would be losing biomass. We found that historically logged forests were recovering biomass near old canals and railways used by the concessions. Lidar detected substantial illegal logging activity—579 km of logging canals were located beneath the canopy. Some patches close to these canals have been logged in the 2011–2104 period (i.e. substantial biomass loss) but, on aggregate, these illegally logged regions were also recovering. Unexpectedly, rapid growth was also observed in intact forest that had not been logged and was over a kilometre from the nearest known canal, perhaps in response to greater aeration of surface peat. Comparing these results with flux measurements taken at other nearby sites, we find that carbon sequestration in above‐ground biomass may have offset roughly half the carbon efflux from peat oxidation. This study demonstrates the power of repeat lidar survey to map fine‐scale forest dynamics in remote areas, revealing previously unrecognized impacts of anthropogenic global change.

Biomass consumption by surface fires across Earth's most fire prone continent - Brett P. Murphy; Lynda D. Prior; Mark A. Cochrane; Grant J. Williamson; David M. J. S. Bowman (Global Change Biology, 2019)
Landscape fire is a key but poorly understood component of the global carbon cycle. Predicting biomass consumption by fire at large spatial scales is essential to understanding carbon dynamics and hence how fire management can reduce greenhouse gas emissions and increase ecosystem carbon storage. An Australia‐wide field‐based survey (at 113 locations) across large‐scale macroecological gradients (climate, productivity and fire regimes) enabled estimation of how biomass combustion by surface fire directly affects continental‐scale carbon budgets. In terms of biomass consumption, we found clear trade‐offs between the frequency and severity of surface fires. In temperate southern Australia, characterised by less frequent and more severe fires, biomass consumed per fire was typically very high. In contrast, surface fires in the tropical savannas of northern Australia were very frequent but less severe, with much lower consumption of biomass per fire (about a quarter of that in the far south). When biomass consumption was expressed on an annual basis, biomass consumed was far greater in the tropical savannas (>20 times that of the far south). This trade‐off is also apparent in the ratio of annual carbon consumption to net primary production ( NPP ). Across Australia's naturally vegetated land area, annual carbon consumption by surface fire is equivalent to about 11% of NPP , with a sharp contrast between temperate southern Australia (6%) and tropical northern Australia (46%). Our results emphasise that fire management to reduce greenhouse gas emissions should focus on fire prone tropical savanna landscapes, where the vast bulk of biomass consumption occurs globally. In these landscapes, grass biomass is a key driver of frequency, intensity and combustion completeness of surface fires, and management actions that increase grass biomass are likely to lead to increases in greenhouse gas emissions from savanna fires.

A reflection on collaborative adaptation research in Africa and Asia - Logan Cochrane; Georgina Cundill; Eva Ludi; Mark New; Robert J. Nicholls; Philippus Wester; Bernard Cantin; Kallur Subrammanyam Murali; Michele Leone; Evans Kituyi; Marie-Eve Landry (Regional Environmental Change, 2017)

Does inherent flammability of grass and litter fuels contribute to continental patterns of landscape fire activity? - Lynda D. Prior; Brett P. Murphy; Grant J. Williamson; Mark A. Cochrane; W. Matt Jolly; David M. J. S. Bowman (Journal of Biogeography, 2017)
Aims To (1) identify the trade‐offs among flammability attributes within grass and litter fuel types; (2) determine how flammability attributes of grass and litter fuels vary across macro‐ecological gradients; and (3) test our hypothesis that inherent flammability attributes of grass and litter fuels scale to satellite‐derived proxies for fire frequency and intensity. Location Continent of Australia. Methods Samples of litter and grass fuels collected from 133 sites across Australia were oven dried, then burnt under controlled conditions. Measurements of ignitability, combustibility and sustainability were made. Estimates of fire frequency and fire radiative power (a proxy for intensity) were derived from satellite imagery. Multivariate analyses were used to identify inter‐relationships among variables and trends across macro‐ecological gradients. Results Flammability was best described by two axes: high rate of combustion versus long duration of burning, and fast rate of spread versus high maximum temperature. As expected, our study confirmed that grass and litter fuel types have inherently differently flammability attributes whereby grass samples burn more quickly, with a higher rate of spread, than litter samples. However, there were also smaller differences in flammability attributes within fuel types, which scaled to rainfall, temperature and soil phosphorus concentrations. In keeping with our hypothesis, we found correlations between inherent fuel flammability attributes and landscape fire activity across the Australian continent. Fire frequency and rate of combustion of grass fuels were both highest in the tropics, and fire intensity and maximum temperature during combustion of litter fuels were highest in temperate areas. Main conclusions At a continental scale, we found landscape fire activity was correlated with inherent flammability of grass and litter fuels. This inherent flammability contributes to observed pyrogeographical patterns that are shaped by climate through its known effects on plant productivity, the abundance of cured grass biomass and fire weather.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Tropical forest fires and biodiversity: dung beetle community and biomass responses in a northern Brazilian Amazon forest - Rafael B. de Andrade; Jos Barlow; Julio Louzada; Fernando Z. Vaz-de-Mello; Juliana M. Silveira; Mark A. Cochrane (Journal of Insect Conservation, 2014)

Pyrogeographic models, feedbacks and the future of global fire regimes - David M. J. S. Bowman; Brett P. Murphy; Grant J. Williamson; Mark A. Cochrane (Global Ecology and Biogeography, 2014)
Conceptual and phenomenological macroecological models of current global fire activity have demonstrated the overwhelming control exerted by primary productivity. Fire activity is very high in savanna regions with intermediate primary productivity, and very low in both densely forested regions with high productivity and arid/cold regions with low productivity. However, predicting future global fire activity using such macroecological models of fire's global ‘niche’ may not be possible because of the feedbacks between fire, climate and vegetation that underpin the fire−productivity relationship. Improving forecasts of global fire activity demands the use of dynamic models to determine how climate, CO 2 , vegetation (i.e. canopy closure and plant functional types) and primary productivity constrain fire and evaluation of the strength of feedbacks amongst these variables.

Pyrogeography, historical ecology, and the human dimensions of fire regimes - Christopher I. Roos; David M. J. S. Bowman; Jennifer K. Balch; Paulo Artaxo; William J. Bond; Mark Cochrane; Carla M. D'Antonio; Ruth DeFries; Michelle Mack; Fay H. Johnston; Meg A. Krawchuk; Christian A. Kull; et al. (Journal of Biogeography, 2014)
In our 2011 synthesis (Bowman et al ., Journal of Biogeography , 2011, 38 , 2223–2236), we argued for a holistic approach to human issues in fire science that we term ‘pyrogeography’. Coughlan & Petty ( Journal of Biogeography , 2013, 40 , 1010–1012) critiqued our paper on the grounds that our ‘pyric phase’ model was built on outdated views of cultural development, claiming we developed it to be the unifying explanatory framework for all human–fire sciences. Rather, they suggest that ‘historical ecology’ could provide such a framework. We used the ‘pyric transition’ for multiple purposes but did not offer it as an exclusive explanatory framework for pyrogeography. Although ‘historical ecology’ is one of many useful approaches to studying human–fire relationships, scholars should also look to political and evolutionary ecology, ecosystems and complexity theories, as well as empirical generalizations to build an interdisciplinary fire science that incorporates human, ecological and biophysical dimensions of fire regimes.

Estimating the impact of changing fertilizer application rate, land use, and climate on nitrous oxide emissions in Irish grasslands - Dong-Gill Kim; Rashad Rafique; Paul Leahy; Mark Cochrane; Gerard Kiely (Plant and Soil, 2014)

Fire regimes of A ustralia: a pyrogeographic model system - Brett P. Murphy; Ross A. Bradstock; Matthias M. Boer; John Carter; Geoffrey J. Cary; Mark A. Cochrane; Roderick J. Fensham; Jeremy Russell‐Smith; Grant J. Williamson; David M. J. S. Bowman (Journal of Biogeography, 2013)
Aim Comparative analyses of fire regimes at large geographical scales can potentially identify ecological and climatic controls of fire. Here we describe A ustralia's broad fire regimes, and explore interrelationships and trade‐offs between fire regime components. We postulate that fire regime patterns will be governed by trade‐offs between moisture, productivity, fire frequency and fire intensity. Location Australia. Methods We reclassified a vegetation map of A ustralia, defining classes based on typical fuel and fire types. Classes were intersected with a climate classification to derive a map of ‘fire regime niches’. Using expert elicitation and a literature search, we validated each niche and characterized typical and extreme fire intensities and return intervals. Satellite‐derived active fire detections were used to determine seasonal patterns of fire activity. Results Fire regime characteristics are closely related to the latitudinal gradient in summer monsoon activity. Frequent low‐intensity fires occur in the monsoonal north, and infrequent, high‐intensity fires in the temperate south, demonstrating a trade‐off between frequency and intensity: that is, very high‐intensity fires are only associated with very low‐frequency fire regimes in the high biomass eucalypt forests of southern A ustralia. While these forests occasionally experience extremely intense fires (> 50,000 kW m −1 ), such regimes are exceptional, with most of the continent dominated by grass fuels, typically burning with lower intensity ( −1 ). Main conclusions Australia's fire regimes exhibit a coherent pattern of frequent, grass‐fuelled fires in many differing vegetation types. While eucalypts are a quintessential A ustralian entity, their contribution as a dominant driver of high‐intensity fire regimes, via their litter and bark fuels, is restricted to the forests of the continent's southern and eastern extremities. Our analysis suggests that the foremost driver of fire regimes at the continental scale is not productivity, as postulated conceptually, but the latitudinal gradient in summer monsoon rainfall activity.

The responses of leaf litter ant communities to wildfires in the Brazilian Amazon: a multi-region assessment - Juliana M. Silveira; Jos Barlow; Rafael B. Andrade; Júlio Louzada; Luiz A. Mestre; Sébastien Lacau; Ronald Zanetti; Izaya Numata; Mark A. Cochrane (Biodiversity and Conservation, 2013)

Comments - Christopher J. Moran; Mark A. Cochrane (Ecology, 2012)

Climate change, human land use and future fires in the Amazon - MARK A. COCHRANE; CHRISTOPHER P. BARBER (Global Change Biology, 2009)
There is increasing consensus that the global climate will continue to warm over the next century. The biodiversity‐rich Amazon forest is a region of growing concern because many global climate model (GCM) scenarios of climate change forecast reduced precipitation and, in some cases, coupled vegetation models predict dieback of the forest. To date, fires have generally been spatially co‐located with road networks and associated human land use because almost all fires in this region are anthropogenic in origin. Climate change, if severe enough, could alter this situation, potentially changing the fire regime to one of increased fire frequency and severity for vast portions of the Amazon forest. High moisture contents and dense canopies have historically made Amazonian forests extremely resistant to fire spread. Climate will affect the fire situation in the Amazon directly, through changes in temperature and precipitation, and indirectly, through climate‐forced changes in vegetation composition and structure. The frequency of drought will be a prime determinant of both how often forest fires occur and how extensive they become. Fire risk management needs to take into account landscape configuration, land cover types and forest disturbance history as well as climate and weather. Maintaining large blocks of unsettled forest is critical for managing landscape level fire in the Amazon. The Amazon has resisted previous climate changes and should adapt to future climates as well if landscapes can be managed to maintain natural fire regimes in the majority of forest remnants.

Conservation Threat of Increasing Fire Frequencies in the Western Ghats, India - NARENDRAN KODANDAPANI; MARK A. COCHRANE; R. SUKUMAR (Conservation Biology, 2004)
The acceleration of processes such as forest fragmentation and forest fires in landscapes under intense human pressures makes it imperative to quantify and understand the effects of these processes on the conservation of biodiversity in these landscapes. We combined information from remote‐sensing imagery and ground maps of all fires in the Mudumalai Wildlife Sanctuary (MWLS) in the Western Ghats of India over 14 years (1989–2002). These spatial data on fire occurrence were integrated with maps of vegetation types found in the MWLS to examine fire conditions in each. We calculated the average fire‐return interval for each of the vegetation types individually and for the MWLS as a whole. Using vegetation data from the larger Nilgiri Biosphere Reserve and the entire Western Ghats region, we conservatively estimated fire‐frequency information for these larger regions. Because the MWLS does not contain tropical evergreen or montane forests, we were unable to estimate fire conditions in these forest types, which represent 31% of all Western Ghats vegetation cover. For the MWLS, all vegetation types had average fire‐return intervals of

Making Sustainability Accessible and Achievable - MARK A. COCHRANE (Conservation Biology, 2004)

Introduction - William F. Laurance; Mark A. Cochrane (Conservation Biology, 2001)

Synergistic Interactions between Habitat Fragmentation and Fire in Evergreen Tropical Forests - Mark A. Cochrane (Conservation Biology, 2001)
The growing prevalence of fragmentation and fire in tropical forests makes it imperative to quantify changes in these disturbances and to understand the ways in which they interact across the landscape. I used a multitemporal series of Landsat images to study the incidence and coincidence of fire and fragmentation in two areas of Pará state in the eastern Brazilian Amazon: Tailândia and Paragominase. In both areas, deforestation and forest fires were quantified for time series of 6–10 years. The Tailândia study area typifies a landscape with the herringbone pattern of government‐settled colonists, and the Paragominas area is dominated by large cattle ranches. In both areas, over 90% of the forests affected by fire were associated with forest edges. Although most burned forest occurred within 500 m of forest edges, some fires occurred in deep forest, several kilometers from any edge. The obvious synergism between forest fragmentation and fire poses serious risks to tropical ecosystems and has important implications for land management.

Forest Fires in the Brazilian Amazon - Mark A. Cochrane; Mark D. Schulze (Conservation Biology, 1998)

Forest Fires in the Brazilian Amazon - Mark A. Cochrane; Mark D. Schulze (Conservation Biology, 1998)